Cognitive skills: Intergenerational transmission by socioeconomic levels - Mayer Foulkes, David; López Olivo, María Fernanda; Serván Mori, Edson (Estudios Económicos de El Colegio de México, 2008)
Using the ENNViH 2002 survey, a switching model shows that significant differences exist in the formation of infant cognitive ability across Mexican social strata. Public policy variables and local economic characteristics are sufficient to detect an important gradient in cognitive abilities and their family determinants in children. Children from lower strata acquire lower cognitive abilities and depend on the satisfaction of more basic needs than children in higher strata. Coefficients for the lower strata are consistent with the existence of wealth restrictions that impede optimal investment in child development.